2022
DOI: 10.1039/d2nj04393a
|View full text |Cite
|
Sign up to set email alerts
|

A DFT study on the formation of heterocycles via iodine(iii)-promoted ring expansion reactions

Abstract: The ring expansion of bicyclic heterocycles bearing an exocyclic double bond promoted by Koser's reagent [hydroxy(tosyloxy)iodobenzene, HTIB] is a mild, practical, and metal-free methodology to access seven-membered rings containing fused...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…During our study of heterocyclic ring expansion reactions using hypervalent iodine, we observed that some of the substrates prepared via Wittig olefination were easily isolated. However, some ketones were decomposed during the work-up process or obtained in very low yields upon exposure to the Wittig reaction [ 23 , 24 ]. To investigate the reason, we decided to observe the decomposition behavior of the expected alkenes via a series of heterocyclic substrates.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…During our study of heterocyclic ring expansion reactions using hypervalent iodine, we observed that some of the substrates prepared via Wittig olefination were easily isolated. However, some ketones were decomposed during the work-up process or obtained in very low yields upon exposure to the Wittig reaction [ 23 , 24 ]. To investigate the reason, we decided to observe the decomposition behavior of the expected alkenes via a series of heterocyclic substrates.…”
Section: Resultsmentioning
confidence: 99%
“…Sample appearance: Yellow viscous oil 1 H NMR (300 MHz, CDCl 3 ) δ: 1.88-1.96 (2H, q, J = 6.2 Hz), 2.42 (2H, t, J = 6.3 Hz), 2.87 (2H, t, J = 6.1 Hz), 3.10 (3H, s), 4.83 (1H, s), 5.10 (1H, s), 6.44 (1H, d, J = 3.3 Hz), 7.03 (1H, d, J = 3.3 Hz). 13 C NMR (75 MHz, CDCl [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20] HTIB has garnered significant interest among researchers because of its economic viability and commercial availability. [21][22][23] The conversion process from 1,2-dihydronaphthalene (1) derivatives into the corresponding indane derivatives using HTIB is highly efficient and straightforward. 2 In our previous work, we utilized 1,2-dihydronaphthalene derivatives as substrates with HTIB to achieve ring-contracted products (indanes) with different functionalities.…”
mentioning
confidence: 99%